Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo paralelo “B” de la carrera de Economía de la Facultad Jurídica, Social y Administrativa, 2023-2024 - Granda Yanza, Michelle Stefania (2024)
The aim of this curricular integration work was to analyse the relationship between the basic cognitive processes of attention and memory and reading comprehension in students of the first parallel cycle "B" of the Economics degree, 2023-2024. A quantitative, descriptive, correlational, cross-sectional, non-experimental design approach was used. The sample of 25 students was administered the d2 test to assess attention and the subscale of the RIAS test to assess memory, as well as the ICLAU instrument to measure reading comprehension. The results obtained indicate that, in the cognitive process of attention, 96% of those evaluated have a low level; in terms of memory, 56% are at a medium level; with regard to the results of the levels involved in reading comprehension, it can be seen that the students are as follows: at high level, literal with 68% and inferential with 72%; at medium level, critical with 40% and appreciative with 60%; and at low level, reorganisation of information with 60%; at the general level of reading comprehension, 68% of students are at low level, which infers difficulties in the interpretation of texts. From the results of the statistical analysis measured by Kendall's Tau-b, between attention and reading comprehension reach a value of 0.199, as well as between memory and reading comprehension a value of 0.183, which, according to the scale of interpretation of Pearson's linear correlation coefficient, are in a range of +0.11 to +0.50 that reveal an average positive correlation, in such a way, the null hypothesis is rejected and the alternative research hypothesis is accepted. Therefore, it is concluded that the basic cognitive processes of attention and memory are related to reading comprehension in the students of the first parallel cycle "B" of the degree of Economics, of the National University of Loja.